Peran Media Papan Jenius untuk Meningkatkan Pemahaman Peserta Didik dalam Penjumlahan Berulang di SDN Karangtumaritis - Fairish Hijriyah Firdaus; Nur Haliza (Journal on Education, 2024)
This study aims to analyze the role of the smart board media in enhancing students' understanding of repeated addition material at SDN Karangtumaritis. The problem faced by students is the low comprehension of basic mathematics, particularly repeated addition, which is influenced by the lack of engaging and interactive learning media. The research method used includes interviews with teachers and a literature review. The results show that the use of smart board media can improve students' understanding in a more enjoyable and interactive way. This media helps students grasp abstract concepts through more concrete visualizations. However, the success of using smart board media is also influenced by student motivation, parental support, and the teacher's ability to manage the media effectively. This research contributes to the development of technology-based learning media that can enhance the quality of mathematics education in elementary schools.